Ответ:
1
Объяснение:
[tex]\frac{3}{4} * \sqrt{0,64} + \frac{1}{6} * \sqrt{5,76} = \frac{3}{4} * 0,8 + \frac{1}{6} * 2,4 = 0,6 + 0,4 = 1[/tex]
Ответ:1
Объяснение:3/4 *0,8(это корень из 0,64) +1/6 * 2,4(корень из 5,76)=
0,6+0,4=1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1
Объяснение:
[tex]\frac{3}{4} * \sqrt{0,64} + \frac{1}{6} * \sqrt{5,76} = \frac{3}{4} * 0,8 + \frac{1}{6} * 2,4 = 0,6 + 0,4 = 1[/tex]
Ответ:1
Объяснение:3/4 *0,8(это корень из 0,64) +1/6 * 2,4(корень из 5,76)=
0,6+0,4=1